The Relationship between Critical Thinking, Self-regulation, and Teaching Style Preferences among EFL Teachers: A Path Analysis Approach - Tahereh Heydarnejad; Azar Hosseini Fatemi; Behzad Ghonsooly (National Research University Higher School of Economics, 2021)
Teachers are world makers. They can change the thinking, attitudes, and lives of their students. Thus, it is essential to study the factors that foster teachers' competency. Critical thinking, self- regulation, and teaching style are some of the factors influencing the effectiveness of teachers. In line with this argument, the present study delved into the possible impact of critical thinking abilities and self-regulatory strategies of English as a foreign language (EFL) teachers on their teaching style preferences. The possible influence of critical thinking abilities on teacher self- regulation was also studied. To do this, Watson-Glaser's Critical Thinking Appraisal (Form 1), the Teacher Self-Regulation Scale (TSRS), and Grasha's Teaching Style Inventory (TSI) were administered to 320 EFL teachers who were teaching at different private language institutions in Iran. A path analysis was utilized to ponder their causal relationships. The findings indicated that teachers with higher critical thinking abilities and self-regulatory skills tend to implement learner- centered styles (namely, Facilitator and Delegator) while teachers with lower critical thinking abilities and self-regulatory skills tend to do the opposite. Moreover, the significant effects of critical thinking on teacher self-regulation were determined. The implications of this study may open up new perspectives into successful pedagogy for policymakers, curriculum designers, and teachers.